Right Prefrontal TMS Disrupts Interregional Anticipatory EEG Alpha Activity during Shifting of Visuospatial Attention - Sauseng, Paul; Freunberger, Roman; Feldheim, Jan F.; Hummel, Friedhelm C. (Frontiers in Psychology, 2011)
Visual attention can be shifted in space without moving the eyes. Amplitude decrease of rhythmical brain activity around 10 Hz (so called alpha activity) at contralateral posterior sites has been reported during covert shifts of visuospatial attention to one visual hemifield. Alpha amplitude increase, on the other hand, can be found at ipsilateral visual cortex. There is some evidence suggesting an involvement of prefrontal brain areas during the control of attention-related anticipatory alpha amplitude asymmetry. However, the exact neural mechanism by which prefrontal cortex influences visual processing has not been completely clear yet. This open question has been studied in detail using a multimodal approach combining transcranial magnetic stimulation (TMS) and multichannel electroencephalography (EEG) in healthy humans. Slow (1 Hz) repetitive TMS inducing an inhibitory effect at the stimulation site was delivered either to right frontal eye field or a control site (vertex). Subsequently, participants had to perform a spatial cueing task in which covert shifts of attention were required to either the left or the right visual hemi-field. After stimulation at the vertex (control condition) a pattern of anticipatory, attention-related ipsilateral alpha increase / contralateral alpha decrease over posterior recording sites could be obtained. Additionally, there was pronounced coupling between (in particular right) FEF and posterior brain sites. When, however, the right prefrontal cortex had been virtually lesioned preceding the task, these EEG correlates of visuospatial attention were attenuated. Notably, the effect of TMS at the right FEF on interregional fronto-parietal alpha coupling predicted the effect on response times. This suggests that visual attention processes associated with posterior EEG alpha activity are at least partly top-down controlled by the prefrontal cortex.